Reaction of glycine with glyoxylate: Competing transaminations, aldol reactions, and decarboxylations. (5th May 2017) - Conley, Mark; Mojica, Mike; Mohammed, Fiaz; Chen, Ke; Napoline, Jonathan W.; Pollet, Pamela; Wang, Jing; Krishnamurthy, Ramanarayanan; Liotta, Charles L.
Abstract: The reactions of glycine, a simple amino acid, with glyoxylate, a simple α‐oxocarboxylate, were investigated in water as a function of time, pH, and temperature and followed using a combination of quantitative 13 C nuclear magnetic resonance and high‐resolution mass spectrometry. Three sets of experiments are reported: (1) reaction of 13 C‐labeled glycine with unlabeled glyoxylate, (2) reaction of unlabeled glycine with 13 C‐labeled glyoxylate, and (3) the reaction of 13 C‐labeled glycine with 13 C‐labeled glyoxylate. Competing transaminations, aldol reactions, and decarboxylations were observed; the mechanistic description for each of these processes is presented. 3‐Hydroxy‐2‐aminosuccinate, a product of reaction between glycine and glyoxylate, was shown to promote both the decarboxylation of glyoxylate and transamination of glyoxylate to glycine. These observations may have implications for the mechanism of attenuation of ethylene glycol toxicity. Abstract : The aqueous reaction of 13 C‐labeled glycine with unlabeled glyoxylate undergoes a transamination process to produce 13 C‐labeled glyoxylate and unlabeled glycine. A competing aldol process produces 2‐amino‐3‐hydroxysuccinate, which promotes the decarboxylation of glyoxylate.